The limits of aesthetic seeing - Pablo Fontoura (Perspectiva Filosófica)
This article explores the concept of sight perception from both cognitive and aesthetic perspectives, by examining the limits of visual attention. It discusses how conscious and unconscious mechanisms can influence what individuals see and may experience aesthetically. It also presents empirical research employing eye-tracking to analyze the visual behavior of visitors of an art exhibition viewing a painting of Japanese artist Isson Tanaka (1908-1977). The study demonstrates that indiscernible aspects of vision interact on the limits of perception, which gives birth to new images. Specifically, the eye-tracking records and uncovers the invisible traces of people's eyes as they are observing the painting, providing opportunities for visual poetics based on sensory input and eye movements. Overall, this interdisciplinary approach contributes to a more thorough understanding of the complexities of visual perception in the arts.